Phenylketonuria—The Guthrie Screening Test—A Method of Quantitation, Observations on Reliability and Suggestions for Improvement - Blumenfeld, Charles M. (1966)
The Guthrie bacterial inhibition assay method of screening neonatal infants for phenylketonuria (pku) initiated mass screening for inborn errors of metabolism. It is a simple, cheap procedure admirably suited to private local use as against private or public central use. However, using parallel fluorometric determinations as a basis for comparison, and 4 mg per 100 ml serum phenylalanine as a presumptive positive threshhold, the Guthrie test yielded 53 per cent “false negatives.” Extrapolating from a combination of our data and reported phenylalanine levels at three days of age or less in proved pku patients, it is estimated the Guthrie test might fail to detect one of 25 pku patients screened at three days of age or less. Means to diminish this risk are considered.